Preparation of single-phase three-component alkaline earth oxide of (BaSrMg)O: a high capacity and thermally stable chemisorbent for oxygen separation. Issue 1 (13th November 2014) - Chen, Xuncai; Jung, Taesung; Park, Jongho; Kim, Woo-Sik
Abstract : Single-phase three-component alkaline earth (BaSrMg)O crystals were prepared by a novel method, which show a high performance in oxygen chemisorption. Abstract : This study presents a preparation method for a single-phase three-component alkaline earth oxide of (BaSrMg)O that is a high capacity and thermally stable chemisorbent for oxygen separation based on the redox reaction cycle of BaO + 1/2O2 ↔ BaO2 . First, single-phase (BaSr)CO3 is co-precipitated based on the reaction of Ba 2+ and Sr 2+ with CO3 2− in a solution, and then transformed to single-phase (BaSrMg)CO3 with the addition of an Mg 2+ solution. When varying the reaction conditions, such as the reactant concentrations of Ba 2+, Sr 2+, Mg 2+, and CO3 2− and the reaction temperature, (Ba0.52 Sr0.06 Mg0.42 )CO3 crystals are identified as the most stable phase. The single-phase (BaSrMg)CO3 is then converted into single-phase (BaSrMg)O by thermal decomposition under an H2 atmosphere at 750 °C. According to a TGA analysis, the chemisorption and desorption of oxygen in (BaSrMg)O are very fast at t 80 = 3.9 min and t 80 = 14 min, respectively. In addition, the chemisorption capacity of (BaSrMg)O is higher at 2.02 mmol g −1 at 700 °C when compared with the chemisorption capacity of BaO/MgO at 1.75 mmol g −1 (Jin et al., Ind. Eng. Chem. Res., 2005, 44, 2942). (BaSrMg)O is also thermally stable due to the inclusion of Mg. Thus, the chemisorption capacity of (BaSrMg)O is unchanged, even over 10 redox reaction cycles. Additionally, the transient oxygen pressure required for the redox reaction of BaO–BaO2 is shifted from 76 mmHg to 148 mmHg due to the inclusion of Sr in (BaSrMg)O. Consequently, the three component alkaline earth oxide (BaSrMg)O can be a highly effective sorbent for industrial applications to oxygen separation in terms of the process design and operation.